2013
DOI: 10.1108/14777261311321761
|View full text |Cite
|
Sign up to set email alerts
|

Senior management leadership, social support, job design and stressor‐to‐strain relationships in hospital practice

Abstract: Purpose -The purpose of this paper is to examine the effect of the quality of senior management leadership on social support and job design, whose main effects on strains, and moderating effects on work stressors-to-strains relationships were assessed. Design/methodology/approach -A survey involving distribution of questionnaires was carried out on a random sample of health care employees in acute hospital practice in the UK. The sample comprised 65,142 respondents. The work stressors tested were quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
13
0
1
Order By: Relevance
“…These findings are supported by previous nursing home studies, for example where higher degrees of supportive leadership were associated with lower job strain and work‐related stress (McGilton et al., ; Orrung Wallin et al., ). Similar findings have also been reported in a study from a hospital context where leaders were shown to have an impact on the social environment, the support given to staff and the strain perceived (Buttigieg & West, ). An extensive review by Skakon et al.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are supported by previous nursing home studies, for example where higher degrees of supportive leadership were associated with lower job strain and work‐related stress (McGilton et al., ; Orrung Wallin et al., ). Similar findings have also been reported in a study from a hospital context where leaders were shown to have an impact on the social environment, the support given to staff and the strain perceived (Buttigieg & West, ). An extensive review by Skakon et al.…”
Section: Discussionsupporting
confidence: 87%
“…The four highest ranked measures at the level of the organization for improving the health of the employees are time to check health status, changes in the ergonomic conditions in the work environment, redefining the work of employees, and conducting training and education in the field of a healthy lifestyle [71]. The findings of a UK study confirm that quality leadership implies social support and an adequate job design, which is a predictor of employee satisfaction and loyalty [72]. For people under labor stress, it is very important that they learn to recognize it and more effectively cope with it in order to preserve their mental health and provide more efficient work.…”
Section: Discussionmentioning
confidence: 92%
“…Further, some scholars use the terms management and leadership interchangeably (Walters, 2016) and argue that there is some degree of overlap between the two (Aruda, 2016). Others question the two concepts and admit the ongoing scholarly debate (Bolden, 2007;Buttigieg andWest, 2013, Gleeson, 2016). Kent (2005) suggests that while there may be a need to define the two concepts independently to ensure clarity in academic debate and research, he argues that the two processes are essentially integrative in nature.…”
Section: Interrelationships Between Management and Leadership Paradigmmentioning
confidence: 99%